SPECIFICITY OF VOCAL AND CHORAL SKILLS FORMATION STUDENTS OF SENIOR CLASSES OF MUSIC SCHOOLS - T.P. Hopkalo (Academy of Cognitive and Natural Sciences, 2009)
Different approaches dealing with formulating pupils' of the last forms vocal-chorus abilities in the classes of chorus in the condition of musical school are considered in this article. The main notions are defined and the peculiarities of accomplishment of vocal-chorus exercises are based.